Transient oxygen-glucose deprivation causes region- and cell type-dependent functional deficits in the mouse hippocampus in vitro - Grube, Paul; Heuermann, Cedric; Rozov, Andrei; Both, Martin; Draguhn, Andreas; Hefter, Dimitri (eNeuro, 2021)
Neurons are highly vulnerable to conditions of hypoxia-ischemia (HI) such as stroke or transient ischemic attacks. Recovery of cognitive and behavioral functions requires re-emergence of coordinated network activity, which, in turn, relies on the well-orchestrated interaction of pyramidal cells (PYRs) and interneurons. We therefore modelled HI in the mouse hippocampus, a particularly vulnerable region showing marked loss of PYR and fast-spiking interneurons (FSIs) after hypoxic-ischemic insults. Transient oxygen-glucose deprivation (OGD) in ex vivo hippocampal slices led to a rapid loss of neuronal activity and spontaneous network oscillations (sharp wave-ripple complexes; SPW-Rs), and to the occurrence of a spreading depolarization. Following reperfusion, both SPW-R and neuronal spiking resumed, but FSI activity remained strongly reduced compared with PYR. Whole-cell recordings in CA1 PYR revealed, however, a similar reduction of both EPSCs and IPSCs, leaving inhibition-excitation (I/E) balance unaltered. At the network level, SPW-R incidence was strongly reduced and the remaining network events showed region-specific changes including reduced ripple energy in CA3 and increased ripple frequency in CA1. Together, our data show that transient hippocampal energy depletion results in severe functional alterations at the cellular and network level. While I/E balance is maintained, synaptic activity, interneuron spiking and coordinated network patterns remain reduced. Such alterations may be network-level correlates of cognitive and functional deficits after cerebral HI.